Discourse-Driven Meaning Construction in Neosemantic Noun-to-Verb Conversions [Meaning Construction In Noun-To-Verb Conversions] - Augustyn, Rafał (Research in Language, 2013)
Neosemantic noun-to-verb conversions such as beer → to beer, door → to door, pink → to pink, etc., constitute a particularly interesting field of study for Cognitive Linguistics in that they call for a discourse-guided and context-based analysis of meaning construction. The present article takes a closer look at the cognitive motivation for the conversion process involved in the noun-verb alterations with a view to explaining the semantics of some conversion formations in relation to the user-centred discourse context. The analysis developed in this article draws from the combined insights of Fauconnier and Turner’s (2002) Conceptual Integration Theory and Langacker’s (2005, 2008) Current Discourse Space.